36 Evaluation and mitigation of the effects of in utero heat stress on pig performance following weaning and transport. (30th November 2020) - Maskal, Jacob M; Duttlinger, Alan W; Kpodo, Kouassi R; McConn, Betty R; Byrd, Christopher; Richert, Brian T; Lay, Donald; Marchant-Forde, Jeremy; Lucy, Matthew; Safranski, Tim; Johnson, Jay S
Abstract: In utero heat stress (IUHS) negatively affects swine productivity and is a growing concern for the swine industry. The study objective was to evaluate and mitigate the negative effects of IUHS on pig performance following weaning and transport. Based on previous research, we hypothesized that IUHS pigs would have reduced performance relative to in utero thermoneutral (IUTN) pigs due to greater maintenance costs and supplementing a nutrient-dense (ND) diet would improve IUHS pig performance to similar levels as IUTN pigs fed a common (C) diet. Therefore, 24 bred gilts were assigned to either thermoneutral (TN; n = 12; 17.5 ± 2.1°C) or heat stress (HS; n = 12; cyclical 27°C to 37°C) conditions for the first half of gestation (d1 to 58) and then TN conditions for the remainder of gestation. At weaning (16.2 ± 0.4 d), pigs (N = 160; 4.78 ± 0.15 kg BW) were transported (loading + transport + unloading) for approximately 12h. Pigs were then blocked into pens (n = 4 pigs/pen) by in utero and dietary treatments which were fed for 14 d (Period-1): IUTN-C (n = 10 pens), IUTN-ND (n = 10 pens), IUHS-C (n = 10 pens), IUHS-ND (n = 10 pens). Following Period-1, all pigs were fed the C diet from d15 to 35 post-weaning and transport (Period-2). Production measures were taken on d 0, 7, 14, 21, 28, and 35 post-weaning and transport to calculate ADG, ADFI, and G:F. During Period-1, ADG was reduced overall (P = 0.03, 10.6%) for IUHS pigs compared to IUTN pigs. Pigs fed ND diets had reduced ADFI during Period-1 (P = 0.02, 8.8%) relative to C fed pigs, regardless of in utero treatment. During Period-2, ADFI was increased (P = 0.03, 4.7%) in ND versus C pigs, regardless of in utero treatment. In summary, increasing the nutrient density of the diet did not rescue the lost productivity of IUHS pigs as indicated by an overall reduction in ADG.